The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4049/jimmunol.174.11.6672
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Generates Putative Soluble CD83 Proteins That Inhibit T Cell Proliferation

Abstract: CD83 is expressed on mature dendritic cells and activated lymphocytes and has been implicated to play an important role during T cell development in the thymus. In contrast, not much is known about the function of CD83 in the periphery. Soluble forms of CD83 have been detected in the serum, but neither the function nor the mechanism of how these soluble forms of CD83 are generated are fully understood. In this study, we report the identification of four different transcripts of CD83 in unstimulated PBMCs. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 37 publications
(34 reference statements)
0
56
2
1
Order By: Relevance
“…However, stimulation of naive T cells in the presence of supernatants from CD83-transduced T cell cultures had no significant effect on the proliferative capacity (data not shown) as it was described for sCD83 (20,24,25). Additionally, CD83-transduced T cells and CD4 ϩ CD25 ϩ Treg cells lost their in vitro suppressive capacity in the absence of cell-cell contact (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, stimulation of naive T cells in the presence of supernatants from CD83-transduced T cell cultures had no significant effect on the proliferative capacity (data not shown) as it was described for sCD83 (20,24,25). Additionally, CD83-transduced T cells and CD4 ϩ CD25 ϩ Treg cells lost their in vitro suppressive capacity in the absence of cell-cell contact (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Further evidence for the inhibitory function of sCD83 isoforms was shown by Dudziak and colleagues (24). They identified four different transcripts of CD83 in unstimulated PBMCs.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Although its exact function is still unknown, various independent studies using soluble forms of CD83 or employing CD83-specific RNA interference provided evidence that this surface molecule is required for efficient DC-mediated T-cell activation [14][15][16][17]19]. Furthermore, it has been shown that CD4 1 single-positive thymocyte development is impaired in CD83 (CD83 À/À ) knockout mice, resulting in pronounced reduction of peripheral CD4 1 T cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a soluble form of CD83 is detectable at low levels in sera derived from healthy individuals, whereas in contrast, elevated levels are present in patients suffering from certain hematological malignancies [8,11]. Notwithstanding the fact that accumulating experimental evidence suggests that CD83 plays an important functional role in the regulation of DCmediated T-cell-specific immune response [12][13][14][15][16][17][18][19], the exact function of CD83 remains poorly understood [20][21][22]. Nevertheless, various disease-related findings suggest that CD83 holds great potential for future therapeutic application [23].…”
Section: Introductionmentioning
confidence: 99%